STUDENTS' SKILL ENHANCEMENT THROUGH DIGITAL ARCHIVE MANAGEMENT AT SMAK IMMANUEL BATAM - Timbul Dompak; Angel Purwanti; Padrisan Jamba; Angeline Wong; Remember To Harefa; Erwin Harefa (PUAN INDONESIA, 2026)
The rapid advancement of digital technology has prompted schools to update not only their learning methods but also their administrative and organizational systems, including archive management. However, many school organizations still rely on manual archiving methods, which often lead to inefficiency, data loss, and limited access to information. This Community Service (PKM) activity was held at SMAK Immanuel Batam to enhance students’ skills in digital archive management, digital law awareness, and the use of Google Sites as a practical archiving platform. The program took place over five sessions during January–February 2025 and involved members of the SMAK Immanuel Student Council aged 16–18 years. The approaches included lectures, guided discussions, hands-on practice, and evaluations conducted before, during, and after the activity. The results showed that participants were enthusiastic and actively engaged throughout the program. Students demonstrated better understanding of digital archiving concepts, legal and ethical issues related to digital information, and practical skills in using Google Sites for archive management. Overall, the PKM activity helped improve students’ digital skills, organizational communication, and ethical awareness, supporting the growth of responsible, digitally literate student organizations.